Water Splitting: Water Splitting Induced by Visible Light at a Copper‐Based Single‐Molecule Junction (Small 28/2021). Issue 28 (15th July 2021) - Fukuzumi, Risa; Buerkle, Marius; Li, Yu; Kaneko, Satoshi; Li, Peihui; Kobayashi, Shuji; Fujii, Shintaro; Kiguchi, Manabu; Nakamura, Hisao; Tsukagoshi, Kazuhito; Nishino, Tomoaki
Abstract : In article number 2008109, Marius Buerkle, Satoshi Kaneko, Tomoaki Nishino, and co‐workers induce the water‐splitting reaction under visible light utilizing a copper‐based single‐molecule junction. A product (hydrogen) and a reactant (water‐molecule) are distinguished by the single‐molecule measurements techniques based on conductance measurement, inelastic electron tunneling spectroscopy, and the first‐principles calculations.